Jurnalisme Advokasi pada Project Multatuli dalam Isu Ibu Kota Negara (IKN) Nusantara - Alwaton, Yogie Alwaton (LPPM Stikosa - AWS, 2023)
This research departs from the premise that the voices of marginalized people are rarely touched by the media. This study aims to analyze the application of advocacy journalism to the Project Multatuli on the issue of the Indonesian National Capital (IKN). Many parties still disagree with the transfer of this capital. Related to this, the media has covered the IKN issue a lot. However, most of the media did not cover much about the impact directly felt by local residents with the transfer of this IKN to their area. In fact, many residents of Penajam Paser Utara also expressed rejection. However, there is no doubt that the mainstream news coverage in Indonesia is dominated by elite perspectives and does not pay attention to the perspectives of citizens who are unable to speak out. So, this is where the role of advocacy journalism comes in. Advocacy journalism is a genre in journalism that focuses on the voices of marginalized groups that are rarely exposed by the media. By using a qualitative content analysis method through one Project Multatuli article title, the result is that advocacy journalism in this alternative media has been well implemented. The five elements of journalism are applied to existing coverage articles. Researcher only found one missing element in this advocacy journalism, which is related to the principle of legality. However, Project Multatuli has carried out a form of advocacy journalism that is in accordance with its passion to raise the voices of marginalized group.